2008
DOI: 10.1029/2008gc002018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of contaminant phases in foraminifera carbonates by electron microprobe mapping

Abstract: [1] The advent of new microanalytical techniques such as electron microprobe mapping (EMP) and laser ablation microsamplers coupled to mass spectrometers (LA-ICP-MS) provides a new array of possibilities to explore in great detail the trace elements distribution in foraminiferal carbonates. Here we apply these techniques to characterize diagenetic phases present in foraminiferal shells from Ocean Drilling Program Site 1240 in the Panama Basin, a region characterized by the presence of manganese-rich minerals i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 34 publications
3
78
2
Order By: Relevance
“…It has been reported that Mn-rich phases can contain trace element contaminants, compromising elemental ratio reconstructions in foraminifera (Pena et al, 2008). In corals, such phases may be Fe-Mn oxide and hydroxide inclusions, contaminant particles (e.g.…”
Section: Effects Of Fe-mn Phases On Intra-skeletal Elemental Ratio Vamentioning
confidence: 99%
“…It has been reported that Mn-rich phases can contain trace element contaminants, compromising elemental ratio reconstructions in foraminifera (Pena et al, 2008). In corals, such phases may be Fe-Mn oxide and hydroxide inclusions, contaminant particles (e.g.…”
Section: Effects Of Fe-mn Phases On Intra-skeletal Elemental Ratio Vamentioning
confidence: 99%
“…In the case of a high intrinsic variability, independent of environmental parameters, more spot measurements will be necessary to obtain a reliable mean value for one specimen or several specimens from the same stable environment (Sadekov et al, 2005;de Nooijer et al, 2014a). Although contamination is an important issue in Mn/Ca measurements (Boyle, 1983;Barker et al, 2003;Pena et al, 2005Pena et al, , 2008, pre-treatment cleaning and a precise targeting of the measurement interval (when using secondary ion mass spectrometry, SIMS, or a LA-ICP-MS), should largely eliminate the potential influence of contaminant phases and/or diagenetic overgrowths (Glock et al, 2012;Koho et al, 2015;McKay et al, 2015). Therefore, the Mn/Ca intra-test variability should ideally not have a diagenetic contribution.…”
Section: Intra-test Variability In Elemental Ratios In Benthic Foramimentioning
confidence: 99%
“…The REE budget of uncleaned sedimentary planktonic foraminifera is dominated by authigenic coatings derived from bottom water (Palmer, 1985;Palmer and Elderfield, 1986;Roberts et al, 2012) that likely comprise iron (oxyhydr)oxides, manganese oxides and/or manganese carbonates (e.g. Boyle, 1983;Haley et al, 2005;Pena et al, 2008;Tachikawa et al, 2013). We suggest that such Mn coatings associated with foraminifera (or with other finer-grained carbonate material within the core) represent the phase that is rapidly dissolved during experiment (iii), and that these are removed by the acetic acid leaching during stage 1 of experiment (ii).…”
Section: Nd Isotopic Evidence On the Phases Involvedmentioning
confidence: 99%